1998
DOI: 10.1021/ja981014w
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Decomposition of Aryl N-(Methoxycarbonyl)sulfamates in Aqueous Media

Abstract: Rate constants and products are reported for the decomposition of aryl N-(methoxycarbonyl)sulfamates 1a − h (range) in aqueous solutions (pH 0−14) at 50 °C. The pK a values at 25 °C of 1a − h are 0.46−2.40. The pH-rate profiles of 1 indicate a rate law that includes three terms:  two pH independent terms, k a in acid and k p around neutral pH, with k a > k p, and a hydroxide ion dependent term, k OH. In acid, product analysis reveals that both S−O (k SO2) and C−O (k CO) bond cleavage reactions are involved. Fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 28 publications
(34 reference statements)
0
12
0
Order By: Relevance
“…[11] However, hydrolysis of N-(oxycarbonyl)sulfamate esters may occur with SÀO bond-breaking if the leaving group on sulfur is much better than that on carbon, as previously observed with certain aryl N-(methoxycarbonyl)sulfamates, ArOSO 2 NH-CO 2 Me. [8] In the latter case, no buffer catalysis was detected in acid for SÀO cleavage, while the analogous CÀO breaking reaction previously reported for phenyl N-(phenylsulfonyl)-carbamate anion (PhSO 2 N À CO À OPh) was unambiguously demonstrated to be general buffer-acid-catalyzed. [7] The different behaviors observed in acid between the C À O and SÀO cleavage reactions of N-(oxycarbonyl)sulfamate esters are discussed.…”
Section: Introductionmentioning
confidence: 75%
See 3 more Smart Citations
“…[11] However, hydrolysis of N-(oxycarbonyl)sulfamate esters may occur with SÀO bond-breaking if the leaving group on sulfur is much better than that on carbon, as previously observed with certain aryl N-(methoxycarbonyl)sulfamates, ArOSO 2 NH-CO 2 Me. [8] In the latter case, no buffer catalysis was detected in acid for SÀO cleavage, while the analogous CÀO breaking reaction previously reported for phenyl N-(phenylsulfonyl)-carbamate anion (PhSO 2 N À CO À OPh) was unambiguously demonstrated to be general buffer-acid-catalyzed. [7] The different behaviors observed in acid between the C À O and SÀO cleavage reactions of N-(oxycarbonyl)sulfamate esters are discussed.…”
Section: Introductionmentioning
confidence: 75%
“…The increased reactivity of the title compound compared to phenyl N-(methoxycarbonyl)sulfamate, [8] by a factor of ca. 4 at 50 8C, is as expected for a mechanism involving a rate-limiting nucleophilic attack at the carbonyl center with different leaving groups such as phenol and methanol.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…2 Recently we have been looking at the reaction mechanisms involved in the aqueous decomposition of unusually weak nitrogen anions of type G 1 -SO 2 N Ϫ CO-G 2 (with G 1 and/or G 2 = alkoxy or aryloxy leaving groups). [2][3][4] Our study of aryl N-(phenylsulfonyl)carbamate esters 1 3 (pK a = 2-3) and phenyl N-(phenoxycarbonyl)sulfamate 2 2 (pK a = 1.18) allowed us to demonstrate that a general acid catalysis may occur in an E1cB process to assist leaving group departure, as observed for the C-O bond cleavage reaction of anions 1 ؊ and 2 ؊ at pH < 4 (Scheme 1). In addition, our kinetic results showed that in the entire pH range both 1 and 2 hydrolyse exclusively by way of their anionic form with 100% C-O bond cleavage.…”
mentioning
confidence: 80%